2013
DOI: 10.1016/j.copbio.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the metabolic engineering of alkaloids in plant systems

Abstract: Plant alkaloids have a rich chemical ecology that has been exploited for medicinal purposes for thousands of years. Despite being highly represented within today’s pharmacopoeia, relatively little is known about the biosynthesis, regulation and transport of these molecules. Understanding how nature synthesizes plant alkaloids will enhance our ability to overproduce—that is, to metabolically engineer—these medicinally useful compounds as well as new-to-nature compounds (with potentially improved bioactivity) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 59 publications
(85 reference statements)
0
56
0
Order By: Relevance
“…On the other, despite patchy knowledge of biosynthetic networks [79,82], accumulation of valuable metabolites strictly dependent on plant growth conditions and developmental stage, and the persistent shortage of efficient transformation protocols, the demand for antitumor alkaloids, vinblastine and vincristine [83] (Fig. 3), drives a tremendous research effort focused on their producer, C. roseus, dubbed the "model non-model system for alkaloid biosynthesis investigation" [62,84].…”
Section: Monoterpenoid Indole Alkaloids (Mias)mentioning
confidence: 99%
“…On the other, despite patchy knowledge of biosynthetic networks [79,82], accumulation of valuable metabolites strictly dependent on plant growth conditions and developmental stage, and the persistent shortage of efficient transformation protocols, the demand for antitumor alkaloids, vinblastine and vincristine [83] (Fig. 3), drives a tremendous research effort focused on their producer, C. roseus, dubbed the "model non-model system for alkaloid biosynthesis investigation" [62,84].…”
Section: Monoterpenoid Indole Alkaloids (Mias)mentioning
confidence: 99%
“…Overall, it has been concluded that the unique hexacyclic nudicaulin skeleton is the result of the biochemical fusion of an indole moiety with a flavonoid‐like C 6 ‐C 3 ‐C 6 unit of phenylpropanoid/polyketide biogenetic origin. The indole biosynthetic pathway is well established15 and proceeds through anthranilate, N ‐(5‐phosphoribosyl)anthranilate as the substrate for indole‐3‐glycerol phosphate synthase, forming indole‐3‐glycerol phosphate, and, further downstream, indole, l ‐tryptophan, and tryptamine. The principal question of whether or not indole, l ‐tryptophan, or tryptamine could act as the key precursor of the indole part of nudicaulins was not determined by the retro‐biosynthetic study and therefore remained to be answered in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, most significant pathways such as photosynthesis and glycolysis/gluconeogenesis (Fig. S16d) also augmented its involvement in regulating primary metabolic pathways as well as synthesis of precursors in upstream of TIA pathway (Aniszewski 2007;Glenn et al 2013). It has also been stated earlier that the initial committed steps in secondary metabolite synthesis are recruited from primary metabolic pathways (Aharoni and Galili 2011;Chu et al 2011).…”
Section: Enrichment Analysis Of Modulesmentioning
confidence: 98%